Interferon-gamma promoter hypomethylation and increased expression in chronic periodontitis - Zhang, Shaoping (2010)
AIM: The goal of this investigation was to determine whether epigenetic modifications in the IFNG promoter are associated with an increase of IFNG transcription in different stages of periodontal diseases. MATERIALS AND METHODS: DNA was extracted from gingival biopsy samples collected from 47 total sites from 47 different subjects: 23 periodontally healthy sites, 12 experimentally induced gingivitis sites and 12 chronic periodontitis sites. Levels of DNA methylation within the IFNG promoter containing six CpG dinucleotides were determined using pyrosequencing technology. Interferon gamma mRNA expression was analysed by quantitative polymerase chain reactions using isolated RNA from part of the biological samples mentioned above. RESULTS: The methylation level of all six analysed CpG sites within the IFNG promoter region in the periodontitis biopsies {52% [interquartile range, IQR (43.8%, 63%)]} was significantly lower than periodontally healthy samples {62% [IQR (51.3%, 74%)], p =0.007} and gingivitis biopsies {63% [IQR (55%, 74%)], p =0.02}. The transcriptional level of IFNG in periodontitis biopsies was 1.96-fold and significantly higher than tissues with periodontal health (p =0.04). Although the mRNA level from experimental gingivitis samples exhibited an 8.5-fold increase as compared with periodontally healthy samples, no significant methylation difference was observed in experimental gingivitis sample. CONCLUSIONS: A hypomethylation profile within IFNG promoter region is related to an increase of IFNG transcription present in the chronic periodontitis biopsies, while such an increase of IFNG in experimentally induced gingivitis seems independent of promoter methylation alteration.